Association of genetic variants in the receptor for advanced glycation end products gene with diabetic retinopathy: A meta-analysis. Issue 39 (September 2016) - Yu, Weihong; Yang, Jingyun; Sui, Wenda; Qu, Bin; Huang, Ping; Chen, Youxin
Abstract: Background: Diabetic retinopathy (DR) is a major sight-threatening diabetic complication. Previous studies have examined the association of DR with multiple genetic variants in the receptor for advanced glycation end products ( RAGE ) gene, with inconsistent results. Objective: To perform a systematic literature search and conduct meta-analyses to examine the association of genetic variants in RAGE with DR. Data sources: PubMed, Cochrane Library, Embase, Google Scholar, and HuGE. Study eligibility criteria and participants: Studies were on human subjects; the studies were case–control ones and included subjects who had DR and those who did not have DR; and the studies provided genotype data for genetic variants in RAGE, separately for subjects who had and did not have DR, or provided odds ratios (ORs) and the 95% confidence intervals (CIs), or provided sufficient data for the calculation of OR and the 95% CI. Study appraisal and synthesis methods: We used OR as a measure of association, and used random-effects model in all the meta-analyses. Between-study heterogeneity was assessed using I 2, and publication bias was evaluated using Egger test. Results: A total of 13 studies met the eligibility criteria and were included in our analyses. We found that Gly82Ser was significantly associated with DR (OR = 2.40, 95% CI: 1.46–3.97; P = 0.001) using a recessive model. -374T/A also showed significant association with DR under a dominant model (OR = 1.21, 95% CI: 1.03–1.43; P = 0.023). We did not find a significant association of DR with other genetic variants in RAGE . Limitations: The number of included studies is small for some genetic variants; duration of diabetes varied across studies; most studies were conducted in Asia; and it is not clear whether the observed association can be generalized to other ethnicities; and we could not control for other potential confounding factors. Conclusions and implications of key findings: We found that Gly82Ser in RAGE showed significant association with DR. More studies with larger sample sizes that control for important risk factors, such as duration of diabetes, are needed to validate our findings. Abstract : Supplemental Digital Content is available in the text